Метод опрацювання синхронних спостережень покриттів зір астероїдом із кількох пунктів - Клещонок, Валерій Володимирович (Київський національний університет імені Тараса Шевченка, 2022)
Розмір і форма астероїда належать до основних його характеристик. Серед багатьох методів отримання цих параметрів може бути використаний метод спостереження покриттів зір астероїдами завдяки можливості залучення великої кількості спостерігачів – аматорів астрономії. Запропоновано новий метод зведення спостережень покриттів із віддалених пунктів, які отримують результати незалежно. Такий метод планується використовувати для проведення спостережень об'єднанням спостерігачів покриттів в Україні.

The size and shape of the asteroid belongs to its main characteristics. Knowledge of these quantities is necessary to determine the density and albedo of asteroids, as well as to understand the fundamental processes of formation and evolution of the solar system. The most popular method for determining these values for asteroids is the photometric method. However, the accuracy of its determination depends on the asteroid heating model used. There are direct methods for determining the shape - measurements using space missions and ground-based interferometers using the largest telescopes. Such methods give accurate results, but are not applicable for mass determinations. The method of observing the occultations of stars by asteroids is available to a wide range of observers, including amateur astronomers. A community of observers is being formed in Ukraine, who plan to start regular observations of these phenomena. When processing such observations, you need to know the exact position of individual observers and have a detailed occultation ephemeris, which can be found at https://asteroidoccultation.com. It is also necessary to have a good time service, which will allow determining the moments of the beginning and end of the occultation with sufficient accuracy. Detailed ephemeris provides information about the trajectory of the shadow on the Earth's surface, indicating the exact time the shadow was in the given coordinates. The ephemeris also contains information about the horizontal coordinates of the star for the center of the shadow at the same time points. The ephemeris also gives the coordinates of the edges of the shadow and their errors, which include the errors of the predetermined asteroid diameter and the errors of the parameters of the asteroid's orbit. The article provides a method for calculating the distance from the observation point to the trajectory of the shadow and a method for calculating the moment of time of the maximum occultation phase for a given observation point. It is possible to combine all independent observations into a single system to determine the diameter and shape of the asteroid knowing these values. This method is planned to be used for processing observations of the Ukrainian community of observers of occultations of stars by asteroids.
Method of processing synchronous observations of star occultation by an asteroid from several points
Keywords: star occultations; asteroids; астероїди; покриття зір